ECHOING VOICES OF COMMUNITY EDUCATION EVENTS: A POETIC SELF-STUDY - Caetano, Ana Paula (Revista Prâksis, 2023)
This paper is a poetic self-study based on a community education project in which the author was involved and in which poetry was a process of social transformation. There is a poetic process of weaving between writings produced during the project, occurred years ago, and writings created for this self-study. Its main purpose is to reflect on this poetic process, questioning how it can continue to illuminate our understandings, develop dialogue and transcend contradictions and ambivalences. A few meaningful events are selected where poetry played a relevant part and where poetic writing, combinins sounds and silence to create a singular musicality, is assumed as a way of deepening and transforming understanding and practice. It is a poetic organisation of rhizomatic relations that facilitates the flow of reflexivity and evocation of the movements experienced during the project and identified as important. They are in accordance with the principles of the project, where dialogical and critical approaches are emphasised. In the final sections the author discuss her positionalities and conflicts as researcher, educator and poet assumed along the process, and conclude by reflecting on some of the main contributions of this paper to the poetic self-study field and poetic inquiry.